2019
DOI: 10.1101/745976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Land use impacts poison frog chemical defenses through changes in leaf litter ant communities

Abstract: AbstractMuch of the world’s biodiversity is held within tropical rainforests, which are increasingly fragmented by agricultural practices. In these threatened landscapes, there are many organisms that acquire chemical defenses from their diet and are therefore intimately connected with their local food webs. Poison frogs (Family Dendrobatidae) are one such example, as they acquire alkaloid-based chemical defenses from their diet of leaf litter ants and mites. It is currently un… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 55 publications
6
19
0
Order By: Relevance
“…Our results pose two hypotheses: First, the distribution of only a few prey species may explain most of the geographic variation in poison frog alkaloids; second, different codistributed prey species may be redundant alkaloid sources. The second hypothesis is supported by a recent analysis of the ants eaten by a different Oophaga species, O. sylvatica (Moskowitz et al, ).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our results pose two hypotheses: First, the distribution of only a few prey species may explain most of the geographic variation in poison frog alkaloids; second, different codistributed prey species may be redundant alkaloid sources. The second hypothesis is supported by a recent analysis of the ants eaten by a different Oophaga species, O. sylvatica (Moskowitz et al, ).…”
Section: Discussionmentioning
confidence: 79%
“…After eliminating those ants that contributed little to the GDM (<0.1%), only nine out of 68 species were retained in the final model. These nine species belong to five genera, of which four ( Anochetus , Brachymyrmex , Monomorium , and Solenopsis ) are known to be eaten by Oophaga or other alkaloid‐sequestering frogs (Clark et al, ; McGugan et al, ; Moskowitz et al, , ). Therefore, a few prey items (i.e., ant species) may contribute disproportionately to the uniqueness of chemical defenses among populations of O. pumilio .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaloids were tentatively identified by comparing this LC-MS/MS dataset to a dataset obtained by gas chromatography / mass spectrometry (GC/MS) from the same samples and used in a previous study exploring environmental variation and chemical defenses in the same frogs [45,46]. The alkaloids detected by GC/MS in the previous study were identified using mass spectral data provided in Daly et al [47].…”
Section: Tissue Collectionmentioning
confidence: 99%
“…Shifts in frog alkaloid composition can occur rapidly over relatively small spatial and temporal scales (Saporito et al 2006, 2007a, Andriamaharavo et al 2015, McGugan et al 2016, Prates et al 2019, Moskowitz et al 2020). For example, independent studies of Oophaga pumilio and Oophaga sylvatica populations only separated by a few hundred meters across a landscape have shown significantly different alkaloid profiles, which appear largely attributed to small‐scale spatial differences in prey availability across habitats (Saporito et al 2006, 2007a, Moskowitz et al 2020).…”
Section: Introductionmentioning
confidence: 99%